2014
DOI: 10.2306/scienceasia1513-1874.2014.40.141
|View full text |Cite
|
Sign up to set email alerts
|

Detection and confirmation of hispolon in the mushroom Phellinus linteus

Abstract: Phellinus linteus (PL), a mushroom known as krathin phiman in Thai, has been used as a traditional medicine in the treatment of various cancers. Hispolon obtained from PL ethanol extracts is a promising anti-cancer compound. In this study, ethanol concentration and extraction time were varied for a soxhlet extraction. The content of hispolon in a crude extract was determined by high performance liquid chromatography with a UV detector. The presence of hispolon in the crude extract was demonstrated by liquid ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…In this study, we investigated the effect of various concentrations at different time of a new natural compound extract from PL: hispolon. Hispolon (6‐(3,4‐dihydroxy‐phenyl)‐4‐hydroxy‐hexa‐3,5‐dien‐2‐one; C 12 H 12 O 4 ), a yellow pigment, is isolated from the P. linteus , has hepatoprotective, anti‐inflammatory, antimetastatic, and antiproliferative effects . It has been shown that hispolon exhibits anticancer effects through inhibition of cell growth, induction of cell cycle arrest, and suppression of metastasis in various types of cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigated the effect of various concentrations at different time of a new natural compound extract from PL: hispolon. Hispolon (6‐(3,4‐dihydroxy‐phenyl)‐4‐hydroxy‐hexa‐3,5‐dien‐2‐one; C 12 H 12 O 4 ), a yellow pigment, is isolated from the P. linteus , has hepatoprotective, anti‐inflammatory, antimetastatic, and antiproliferative effects . It has been shown that hispolon exhibits anticancer effects through inhibition of cell growth, induction of cell cycle arrest, and suppression of metastasis in various types of cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…The chemopreventive efficacy of curcumin has garnered significant attention, due to its low nonspecific toxicity to normal cells. Hispolon, a yellow phenolic pigment isolated from a mushroom species, Phellinus linteus [4], is a polyphenol structurally similar to curcumin, and has been investigated and found effective for anti-inflammatory [5], antioxidant [6], and anticancer [7,8] properties. The anticancer potential of hispolon is possibly due to its ability to halt the cell cycle in several cancer cells, to induce apoptosis by activation of caspase-3, caspase-8 and caspase-9, to inhibit NF-kB signaling, or to downregulate Akt signaling pathways [9].…”
Section: Introductionmentioning
confidence: 99%
“…Hispolon (6-(3,4-dihydroxy-phenyl)-4-hydroxy-hexa-3,5-dien-2-one; C 12 H 12 O 4 ), a yellow pigment and a natural polyphenol, isolated from the Phellinus igniarius and Phellinus linteus, is structurally similar to curcumin, but lacks one aryl moiety (Balaji et al, 2015;Hyang et al, 2015;Toopmuang et al, 2014;Wu et al, 2014). It exhibits protective effect against acute liver damage (Huang et al, 2012), in ammation (Chang et al, 2011), metastasis (Huang et al, 2010), proliferation of cancer cells (Huang et al, 2011), generation of ROS (Ali et al, 1996), estrogenesis in breast cancer (Hyang et al, 2015), (Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%